Changes in Plasminogen Activator Activity and Plasmin Inhibition in the Pig During Experimental Hypovolaemia - Smokovitis, A; Wagner, M; Starlinger, M; Opitz, A; Binder, B R (Thrombosis and Haemostasis, 1985)
A markedly decreased plasminogen activator activity (PAA) was seen in lung, heart and kidney after experimental hypovolemia in the pig. In 2 of 12 cases, an increased PAA was found in liver and spleen. In skeletal muscle, skin, sciatic nerve and in 10 of 12 cases in liver and spleen PAA was unchanged. A slightly increased plasmin inhibition was noted only in the lung. These changes in tissue PAA were reflected by an increase in the PAA of euglobulin fractions concomitant with a decrease in antiplasmin activity in the blood samples obtained during the bleeding experiments.
Keywords: Haemorrhagic hypotension; Fibrinolysis; Plasminogen activator activity; Plasmin inhibition; Pig